Financial inclusion and development in the least developed countries in Asia and Africa - Antonella Francesca Cicchiello; Amirreza Kazemikhasragh; Stefano Monferrà; Alicia Girón (Journal of Innovation and Entrepreneurship, 2021)
The purpose of this paper is to investigate the relationship between the financial inclusion index and development variables in the least developed countries in Asia and Africa by using annual data of 42 countries for the period 2000-2019. The pooled panel regression and panel data analysis technique are used to explore this relationship. The empirical finding indicates that economic growth leads to financial inclusion. Unemployment and literacy rates are among the factors contributing to financial inclusion, and it is observed that women are more vulnerable than men are to lack financial inclusion. In less developed countries, the economy relies heavily on agriculture, and people are less financially inclusive when they live in rural areas of these countries. Also, pay inequality reduces financial inclusion rates and has a negative impact on development. The low financial inclusion rate reduces the levels of development in these countries. The results of this study can lead to the development and empowerment of vulnerable groups in the studied countries. In order to improve the conditions for development, policymakers should consider policies that enhance literacy, eliminate gender inequality and increase pay equality.
Keywords: G21; J16; O16; O23; O50; 650; Financial inclusion; Gender; Economic development; Financing policy